Effects of inhalation and propofol anaesthesia on postoperative cognitive dysfunction in elderly noncardiac surgical patients: A systematic review and meta-analysis. Issue 43 (29th October 2021) - Pang, Qian-Yun; Duan, Li-Ping; Jiang, Yan; Liu, Hong-Liang
Abstract: Background: Postoperative cognitive dysfunction (POCD) is a very common event in elderly noncardiac surgical patients. The effects of inhalational anaesthetics and propofol on the incidence of POCD and postoperative cognitive status at different time points after surgery are currently unclear. Methods: We searched the Embase, Medline, Cochrane Library, and Web of Science databases for randomized controlled trials (RCTs), in which inhalation anaesthesia and propofol anaesthesia were compared. The incidence of POCD or postoperative cognitive status was assessed in elderly patients undergoing noncardiac surgery. Results: Fifteen RCTs with 1854 patients were included in this meta-analysis. The incidence of POCD on postoperative Days 2–6 after propofol anaesthesia was markedly lower than that after inhalation anaesthesia (risk ratio (RR): 0.37, 95% confidence interval (CI): 0.15–0.88, P = .025), and Mini-Mental State Examination (MMSE) scores after propofol anaesthesia were substantially higher than those after inhalation anaesthesia (standard mean difference (SMD): 0.59, 95% CI: 0.07–1.11, P = .026). The levels of interleukin-6 (IL-6) and tumour necrosis factor-α (TNF-α) were much lower after propofol anaesthesia than after inhalation anaesthesia (SMD: -2.027, 95% CI: -3.748– -0.307, P = .021; SMD: -0.68, 95% CI: -0.93– -0.43, P < .001). Conclusions: The moderate evidence from this meta-analysis shows that, in elderly noncardiac surgical patients, propofol anaesthesia is superior to inhalation anaesthesia for attenuating of early POCD incidence, and low-level evidence shows that cognitive status is higher and systemic inflammation is less severe after propofol anaesthesia in the early days after surgery. Limitations: The sample size was not sufficiently large for systemic inflammation, and the tools to identify POCD were not uniform in the included studies. Abstract : Supplemental Digital Content is available in the text